An instance of East-West confusion in Chinese Umbelliferae, or Arracacia out of Asia! - Constance, L. (Edinburgh Journal of Botany, 2010)
Franchet (1894) described two species from Yunnan as Arracacha (= Arracacia) delavayi and A. peucedanifolia, respectively, in a genus hitherto known only from Mexico to Bolivia in the New World. Wolff (1925) made A. delavayi the type of his new genus Physospermopsis, but neither de Boissieu (1906), Wolff, nor Norman could find an appropriate generic home for A. peucedanifolia. In 1980, Sheh and Shan established the new genus Cyclorhiza with one species and a second taxon which became C. major (M.L. Sheh & R.H. Shan) M.L. Sheh in Flora Reipublicae Popularis Sinicae. This work does not mention either A. peucedanifolia or Cenolophiwn chinense M. Hiroe (1958), which was based on similar material. The correct name for A. peucedanifolia is Cyclorhiza peucedanifolia (Franch.) Constance, comb. nov. and the genus Arracacia is to be excluded from Asia.
Keywords: Apiaceae; Cenolophium; Cyclorhiza